PELAKSANAAN KODE ETIK PROFESI GURU BIMBINGAN DAN KONSELING - Rahardjo, Susilo; Kusmanto, Agung Slamet (JURNAL KONSELING GUSJIGANG, 2017)
The professional ethic codes is the moral basis and guidance of professional behavior that is upheld, implemented and secured by every member of the professional organization of guidance and counseling of Indonesia, including the Guidance and Counseling’s Teacher of SMP/MTs (Secondary Schools) in Kudus Regency. The result of the survey on the implementation of the professional ethic codes towards the Guidance and Counseling’s Teachers of Secondary Schools in Kudus Regency shows that the scores and categories are as follows: Introduction 85% (Very High); Qualifications, Competencies, and Activities 84% (Very High); Implementation of Service 78% (High); Violations and Sanctions 33% (Very Low); and The total score average is 74.22% (High). The Professional Ethic Codes of Counselor in Secondary Schools (MTs/SMP) in Kudus Regency have been well implemented by teachers which means that teachers of Guidance and Counseling at schools have applied and obey the Professional Ethic Codes.